POSISI DPRD DALAM UU NO. 32 TAHUN 2004 - FITRIYAH, FITRIYAH (Politika: Jurnal Ilmu Politik, 2010)
AbstractLaw No. 22/1999 on local governance gives more power to Local Assemblies (DPRD) as"the local legislative body". The Law No. 22/1999 lays down their rights and responsibilities in somedetail. These include overseeing budgets, drawing up local regulations to select governor, mayor ordistrict head (bupati), including the power to call the governor, mayor or district head (bupati) toaccount. The Law No. 22/1999 was revised by Law No. 32/2004. Under Law No. 32/2004 DPRD haveloss many powers, including the power to select the governor, mayor or bupati. Today’s main issue isstrengthening the position of DPRD. This article shows up that the main issue not to improve agreater role of DPRD but by develops their capacity.Keywords: kewenangan, badan legislatif daerah, unsur pemerintahan daerah